O111
O111
O111
1
and
X 0 1, if 2k + 1 = 0;
0 X
since 2k + 1 = = 0,
g0 = qk = 0 · qk 0, if 2k + 1 6= 0
2k + 1
k∈N k∈N because k ∈ N yields 2k + 1 6= 0
= 0.
Hence, 0
f0 qg0 1 q·0 1 0 1 q
= = = .
g0 f 0 0 1 0 1 1 1
In other words, (1) holds for n = 0. This completes the induction base.
Induction step. Let N ∈ N. Assume that (1) holds for n = N. We have to show
that (1) holds for n = N + 1 as well.
The recurrence of the binomial coefficients shows that
N +1 N N
= + for every a ∈ Z. (6)
a a a−1
n
(Here, we are using the convention that = 0 if a < 0.)
a
Since (1) holds for n = N, we have
N
fN qgN 1 q
= . (7)
gN fN 1 1
But the definitions of fN +1 and gN +1 yield
X N + 1 X N N
k
fN +1 = q = + qk
k∈N
2k k∈N
2k 2k − 1
N +1 N N
as = + (by (6), applied to a = 2k)
2k 2k 2k − 1
X N X N X N X N
k k k
= q + q = q + qk
k∈N
2k k∈N
2k − 1 k∈N
2k k∈N;
2k − 1
k≥1
P P
here we replaced the sign by an sign, since the addend for k = 0 is zero
k∈N k∈N;
k≥1
N N N
= (as = = 0 for k = 0)
2k − 1 2·0−1 −1
X N X N
= qk + q k+1
k∈N
2k k∈N |
2 (k + 1) − 1 |{z}
{z } =q·qk
N
=
2k + 1
(here we substituted k + 1 for k in the second sum)
X N X N
k
= q +q q k = fN + qgN = 1 · fN + q · gN
k∈N
2k k∈N
2k + 1
| {z } | {z }
=fN =gN
(by the definition of fN ) (by the definition of gN )
2
and
X N + 1 X N N
k
gN +1 = q = + qk
k∈N
2k + 1 k∈N |
2k + 1 2k + 1 − 1
{z }
N N
= +
2k
+ 1 2k
N N
= +
2k 2k + 1
N +1 N N
as = + (by (6), applied to a = 2k + 1)
2k + 1 2k + 1 2k + 1 − 1
X N N
= + qk
k∈N
2k 2k + 1
X N X N
k
= q + q k = fN + gN = 1 · fN + 1 · gN .
k∈N
2k k∈N
2k + 1
| {z } | {z }
=fN =gN
(by the definition of fN ) (by the definition of gN )
Hence,
fN +1 qgN +1 1 · fN + q · gN q (1 · fN + 1 · gN ) 1 · fN + q · gN 1 · qgN + q · fN
= =
gN +1 fN +1 1 · fN + 1 · gN 1 · fN + q · gN 1 · fN + 1 · gN 1 · qgN + 1 · fN
N N +1
1 q fN qgN 1 q 1 q 1 q
= = = .
1 1 gN fN 1 1 1 1 1 1
| {z }
N
1 q
=
1 1
(by (7))
In other words, (1) holds for n = N + 1. This completes the induction step. Thus, the
induction proof is complete, so that (1) is proven for all n ∈ N.
Now, (2) follows from
n
2 2 fn qgn 1 q
fn − qgn = fn · fn − qgn · gn = det = det (by (1))
gn fn 1 1
n
1 q
= det = (1 · 1 − q · 1)n = (1 − q)n .
1 1
3
For any a ∈ N and b ∈ N, we have
a+b
fa+b qga+b 1 q
= (by (1), applied to n = a + b)
ga+b fa+b 1 1
a b
1 q 1 q
= ·
1 1 1 1
| {z }
| {z }
fa qga fb qgb
= =
ga f a gb f b
(by (1), applied (by (1), applied
to n=a) to n=b)
fa qga fb qgb fa · fb + qga · gb fa · qgb + qga · fb
= · =
ga f a gb f b ga · fb + fa · gb ga · qgb + fa · fb
fa fb + qga gb q (fa gb + ga fb )
= .
fa gb + ga fb fa fb + qga gb
Thus, fa+b = fa fb + qga gb and ga+b = fa gb + ga fb , so that (4) and (5) are proven. For
every n ∈ N, we have
1 1 2 1 1
2 2 2
= · · qg2n = · · f2n − f2n − qg2n
4 q 4 q
| {z }
|{z} =1
1 (by (8))
=
2
(since q=2)
1 1 2
1 2 1
= · · f2n −1 = f2n − 1 = (f2n − 1) (f2n + 1)
4 2 8 8
1 f2n − 1 f2n + 1 1 f2n − 1 f2n − 1
= · · = · · +1
2 2 2 2 2 2
4
f2n − 1
for every n ∈ N. Since ∈ Z for every n ∈ N (since
2
2n P 2n k
20 + 2 −1
P 2n k P 2n k
2·0 k∈N; 2k
q −1 2 −1
f2n − 1 k∈N 2k k∈N 2k k≥1
= = =
2 2 2 2
P 2n k
1 + 2 −1
k∈N; 2k
k≥1 2n 0 2n 0
= since 2 = 2 =1·1=1
2 2·0 0
P 2n k
2
k∈N; 2k
k≥1
X 2n
= = 2k−1 ∈ Z
2 k∈N;
2k
k≥1
), this yields that fn2 gn2 is a triangular number for every n ∈ N. This is exactly what
the problem asked us to prove.
Remark. Theorem 1 could be proved more quickly using the binomial formula
√ n √ n
applied to 1 + q and 1 − q . However, such a proof would fail if we replace
R by a field of characteristic 2 and q is a square in that field. The proof given above
works over any field and for any q. (Then again, from a deeper viewpoint, it is just a
straightforward elementarization of the proof using the binomial formula.)